Percutaneous Pinning of Distal Radius Fractures Using Hematoma Block: Outcomes in Our Center - Ralahy Malinirina Fanjalalaina; Ravololoniaina Tiana; Razafimahandry Henri Jean Claude (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2016)
Surgical treatment is indicated for displaced and unstable distal radius fractures. Kapandji percutaneous pin fixation technique is widely practiced on account of its efficiency and relative reproducibility. The purpose of this study was to demonstrate no difference in terms of patients' residual pain between Kapandji-pinning and closed reduction associated with cast immobilization using both intra-focal anesthesia in the treatment of unstable distal radius fractures. The secondary objective was to evaluate the surgical outcomes of Kapandji pinning using intra-focal anesthesia. This is a single-center prospective comparative study from January to June 2013. Patients were randomly assigned to Group 1 or Group 2. The first group underwent Kapandji-pinning of the fracture. The second group was treated with closed reduction and cast immobilization. Intra-focal anesthesia was used in both groups. Thirty-eight patients were included in the study; 18 in Group 1 and 20 in Group 2. There was no difference between groups for the patients' average residual pain. There was more secondary displacement in Group 2 than in Group 1 (13 vs 5; p=0,01). Kapandji-pinning using intra-focal anesthesia can be an alternative treatment for patients having extra-articular distal radius fracture with posterior displacement.